Policy effect of the “blue sky plan” on air pollution, ESG investment, and financial performance of china’s steel industry - Lu, Peiyao; Hamori, Shigeyuki; Tian, Shuairu (Frontiers in Environmental Science, 2022)
This study aims to examine the policy effects of the “Three-Year Action Plan to Win the Blue Sky War” on the steel industry and air pollution in China. Specifically, we analyze the impact of the “Blue Sky Plan” on Chinese steel companies' ESG investments, corporate financial performance, and the emissions of sulfur dioxide and nitrogen oxides in the exhaust gas. Our evidence suggests that ESG investment in steel companies can lead to a significant decrease in financial performance. The “Blue Sky Plan" compensated for about one-third of corporate ESG investment losses and played a significant role in promoting the ESG investment of steel companies. In addition, we found that after the implementation of the “Blue Sky Plan,” the emissions of sulfur dioxide and nitrogen oxides in the exhaust gases were significantly reduced.